Composição da dieta e sua associação com o fenótipo metabolicamente saudável em indivíduos da linha de base do ELSA-BRASIL - Alves, Sara Rodrigues (2017)
INTRODUCTION: Obesity is a multifactorial disease and is considered a risk factor for the development of chronic non communicable diseases. However, there are obese individuals who do not present an unfavorable metabolic profile, denominated in the literature as metabolically healthy obese. It is believed that genetic factors and lifestyle factors among other characteristics may influence the determination of this group. Among the described lifestyle factors, food consumption should be highlighted; the use of this variable in epidemiological studies tends to be limited and, consequently, inconclusive. Thus, the objective of this research was to investigate the association between dietary intake and metabolically healthy obesity. METHODS: The research population came from the baseline of ELSA-Brasil (N = 15,105) and after exclusion criteria, the final sample was of 2,033 individuals. They were classified as obese when BMI ≥ 30 kg / m², metabolic criteria adopted by IDF and NHANES were used to define the outcome. Variables were collected using questionnaires and physical, hemodynamic and biochemical tests. The association between exposure, adjust and outcome variables was tested using chi-square and tstudent tests; those that presented significance levels below 0.10 were inserted in the adjusted model of the binary logistic regression. All analysis was performed using SPSS version 23 and significance level of 5%. RESULTS: The mean age of participants was 53.3 years and 1130 (55.6%) were women. A prevalence of 19.3% of metabolically healthy obesity was observed for this sample. The younger age, female gender, better self-perception of health, active employment status, strong physical activity levels, lower BMI and lower weight gain since 20 years of age were positively associated with the healthy phenotype. Regarding food consumption, total lipids (g) (OR 1.007), including saturated fat (g) (OR 1.017) and trans fat (g) (OR 1.119) were positively associated to the outcome even after adjustment for the socioeconomic, health and lifestyle variables. CONCLUSION: It can be concluded that nutrient intake was associated with metabolically healthy obesity in a manner different from the usual recommendations in dietary guidelines, even after adjustment; demonstrating that, even though nutritional differences are quite small, healthy individuals have poorer food behavior; such a finding suggests the existence 8 of an association between food consumption and the metabolically healthy phenotype. Also, other factors, not addressed by the present research, such as epigenetic issues or the interactions between food and nutrients (eating patterns) may improve the comprehension of the relation between metabolically healthy obesity and diet.